2020
DOI: 10.12965/jer.2040188.094
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill exercise activates ATF3 and ERK1/2 downstream molecules to facilitate axonal regrowth after sciatic nerve injury

Abstract: The purpose of this study was to investigate the effect of treadmill exercise on activating transcription factors such as activating transcription factor 3 (ATF3) and extracellular signal-regulated kinase (ERK1/2) signaling pathway to facilitate axonal regrowth after sciatic nerve injury (SNI). The experimental rats divided into the normal control (n = 10), sedentary groups for 7 (n= 10) and 14 days (n= 10) post crush, exercise group for 7 (n= 10) and 14 days (n= 10) post crush (dpc). The rats in exercise grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Previous studies reporting on nerve regeneration and regular exercise suggested that that neurotrophin 4/5 and BDNF were required for the early stage of regeneration axons in peripheral nerves, and they were continuously increased for a 4weeks treadmill exercise after SNI ( English et al, 2005 ). In addition, Kim et al (2020) investigated that low-intensity treadmill exercise upregulated expression level of GAP-43 in the injured axons and ipsilateral DRG after SNI. These findings in previous studies support our findings that regular treadmill walking might be a valid therapeutic method for facilitating axonal regrowth in the injured sciatic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reporting on nerve regeneration and regular exercise suggested that that neurotrophin 4/5 and BDNF were required for the early stage of regeneration axons in peripheral nerves, and they were continuously increased for a 4weeks treadmill exercise after SNI ( English et al, 2005 ). In addition, Kim et al (2020) investigated that low-intensity treadmill exercise upregulated expression level of GAP-43 in the injured axons and ipsilateral DRG after SNI. These findings in previous studies support our findings that regular treadmill walking might be a valid therapeutic method for facilitating axonal regrowth in the injured sciatic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are no significant differences TEX and TEX+BMSC groups. In previous studies, GAP-43 started to be expressed from the early phase of the sciatic nerve regeneration and treadmill exercise continuously increased from 1 day to 2 weeks after SNI (Kim et al, 2020;Seo et al, 2009). BMSC-dervied extracellular vesicles treatment also promoted the functional recovery and nerve regeneration after SNI through upregulation of GAP-43 protein (Ma et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, exercise upregulates ATF3 transcription in skeletal muscle after exercise ( Fernández-Verdejo et al, 2017 ). Treadmill exercise can promote sciatic nerve injury regeneration through ATF3 upregulation ( Kim et al, 2020 ). In contrast, silencing of the ATF3 family gene can inhibit exercise-induced angiogenesis ( Fan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%